Design and implementation of upconversion RF mixers from 2.4GHz to 11.4Ghz - Gonzalez, Ariston N.; Morales, Paulo Jessie R.; See Go, Jonathan A. (2011)
The project dealt with the design of three different upconversion RF mixers that translate a 2.4GHz input signal to 11.4GHz using a 9GHz local oscillator. The first mixer circuit is a single-balanced mixer using a rat race coupler, the second one is a single-balanced mixer using a quadrature hybrid coupler and the third is a double-balanced ring mixer using quadrature hybrid couplers. Schottky diode pairs, namely Agilent HSMS8202 diode pair, were used as the switching components for the three mixer circuits. The couplers, filters and then the mixer circuits were modeled and simulated using the software Ansoft RF Designer. Emphasis was given on the conversion loss of the mixers and the different factors that affect it. Layout manufacturability was considered in the design. Acceptable conversion losses of around -10dB were obtained in software and the desired 11.4GHz output signal is at least 20dB more powerful than the strongest unwanted signal for all three mixers. The designs were then fabricated on high frequency laminates, namely R/T Duriod 5880 boards. Both in-house and outsourced fabrications were conducted. Three different prototypes were produced. These prototypes were then tested in the Wireless Communications Engineering Laboratory using RF signal generators and a spectrum analyzer. Testing was also done in the laboratory of Remec Broadband Wireless Inc. to validate the results. The output spectrum was observed with emphasis on the output power at 11.4GHz. Discrepancies between the simulated results and actual measured parameters were then recorded and evaluated.
Undergraduate student project (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Microwave mixers -- Testing; Radio frequency integrated circuits; Single balanced diode mixer (SBDM).